Calcium Signaling and Transcriptional Regulation in Cardiomyocytes. Issue 8 (29th September 2017) - Dewenter, Matthias; von der Lieth, Albert; Katus, Hugo A.; Backs, Johannes
Abstract : Calcium (Ca 2+ ) is a universal regulator of various cellular functions. In cardiomyocytes, Ca 2+ is the central element of excitation–contraction coupling, but also impacts diverse signaling cascades and influences the regulation of gene expression, referred to as excitation–transcription coupling. Disturbances in cellular Ca 2+ -handling and alterations in Ca 2+ -dependent gene expression patterns are pivotal characteristics of failing cardiomyocytes, with several excitation–transcription coupling pathways shown to be critically involved in structural and functional remodeling processes. Thus, targeting Ca 2+ -dependent transcriptional pathways might offer broad therapeutic potential. In this article, we (1) review cytosolic and nuclear Ca 2+ dynamics in cardiomyocytes with respect to their impact on Ca 2+ -dependent signaling, (2) give an overview on Ca 2+ -dependent transcriptional pathways in cardiomyocytes, and (3) discuss implications of excitation–transcription coupling in the diseased heart.